PROTOTYPE RICE DRYER UNTUK OPTIMALISASI PRODUKTIVITAS PASCAPANEN - Tika Rukmana; Muhammad Anwar (Journal of Innovative and Creativity, 2025)
Drying is a critical stage in the post-harvest process of rice to maintain the quality and shelf life of the grain. In Indonesia, traditional sun-drying methods are still widely used, which are highly dependent on weather conditions and require significant time and labor. These limitations often lead to grain moisture levels exceeding the ideal range set by the Indonesian National Standard (SNI 6128:2020), which is 13–14%, thereby reducing the quality and market value of the rice. This study aims to design and implement a semi-automatic rice dryer system based on the Arduino Mega 2560 microcontroller to regulate temperature, humidity, and grain moisture levels automatically. The system utilizes DS18B20 sensors for temperature, DHT22 for humidity, and a grain moisture sensor, while controlling fans, heaters, and agitators through programmed logic. Test results show that the prototype can reduce grain moisture levels more efficiently and consistently than traditional methods, with sensor readings falling within acceptable accuracy tolerances. This tool is expected to provide an effective solution for improving rice drying quality and supporting overall farmer productivity